Advertising Club of Baltimore (written on back of photograph). Edward R. Murrow with, from left to right: Unidentified, Governor Theodore R. McKeldin, Murrow, Hammerman, and unidentified. (Tufts Archival Research Center, 2005)
8x10. February 2, 1957.